A High Output Triboelectric–Electromagnetic Hybrid Generator Based on In‐Phase Parallel Connection. Issue 6 (5th January 2022) - Zhao, Tiancong; Niu, Bo; Xie, Guangci; Hu, Chao; Liu, Boying; Xu, Minyi; Ma, Yong
Abstract: With the advent of carbon neutrality, renewable energy installations are being upgraded toward miniaturization, low cost, and high conversion efficiency. Thus, a high output triboelectric–electromagnetic hybrid generator based on in‐phase parallel connection (IP‐HG) is proposed. The output characteristics of both TENG (triboelectric nanogenerator) and EMG (electromagnetic generator) can be effectively complemented to provide excellent output over a wide range of operating frequencies. By connecting multiple TENGs in parallel with EMGs in the same phase respectively, cumbersome rectification elements and wiring can be eliminated, and the energy output of the device can be greatly increased. The output characteristics and advantages of the IP‐HG are systematically investigated, including the material of the TENG, the rotation speed, the combination of dielectrode, and their effect on the electrical output of the IP‐HG. The short‐circuit current of 63 mA, open‐circuit voltage of 80 V, and an instantaneous output power density of 610 W m −3 is obtained by using a full‐wave rectifier circuit at 243 rpm, which can charge a 470 μF capacitor to 1 V in 0.2 s. A maximum output efficiency reaches 36.162% at 189 rpm. In addition, the IP‐HG can continuously power a commercial sensor and three 5 W DC light bulbs at very low rotational speeds. The reported IP‐HG offers an efficient and sustainable design approach to the development of hybrid harvesters. Abstract : This work developed a high output triboelectric‐electromagnetic hybrid generator based on in‐phase parallel connection (IP‐HG). By connecting multiple units in in‐phase, the output of IP‐HG can be greatly increased over a wide range of frequencies. A maximum output efficiency reaches 36.162% at 189 rpm and an instantaneous output power density of 610 W m −3 at 243 rpm.